Implications of Genetic Structure for Aquaculture and Cultivar Translocation of the Kelp Ecklonia radiata in Northern New Zealand - Nepper-Davidsen, Jacob; Magnusson, Marie; Glasson, Christopher R. K.; Ross, Philip M.; Lawton, Rebecca J. (Frontiers in Marine Science, 2021)
The fast expansion of the global seaweed aquaculture industry has created an interest in translocating seedlings cultivated from wild type brood stock. However, such translocations must be applied with caution as introduced cultivars can reduce genetic structure and diversity of wild populations. An understanding of the genetic structure and connectivity of target species is required to guide decision making around aquaculture translocation activities. In this study we used 14 microsatellite loci in a three-level hierarchical sampling design to analyze the genetic structure and connectivity of the native kelp Ecklonia radiata across 12 sites among four geographic regions (Northland, Bay of Plenty, Gisborne, and Wellington) in the North Island of New Zealand. Our aim was to provide guidance for translocation of cultivars to prevent the introduction of locally absent genotypes of E. radiata. Strong genetic structure and low geneflow were observed at all hierarchical levels, indicating the presence of multiple genetically distinct sub-populations. On a regional scale, high genetic differentiation was found between the Wellington region and the other three regions (FST = 0.407–0.545), and within regions most sites were significantly different (measured by pairwise FST) with high relatedness found between individuals within sites (mean 28.2% ± 0.7 SE). Bayesian modeling and redundancy analysis showed a high degree of genetic clustering and indicate that ocean currents and other factors that have resulted in biogeographical breaks along the coast are likely to be the main factors shaping genetic structure and connectivity of E. radiata on the North Island, rather than isolation by distance. Based on these findings, we recommend that that cultivars of E. radiata should not be translocated outside their area of origin to avoid introducing locally absent genotypes to local sub-populations.